Students’ preconceived notion about statistics - Rimkuvienė, Daiva; Kaminskienė, Janina; Raškinienė, Danutė (Lietuvos matematikos rinkinys, 2008)
The research aim of this paper is to describe the attitude of LUA students towards statistics and to present recommendations for improvement of the teaching and learning processes of this subject. Basic method for assessing student’s attitudes is Survey of Attitudes Toward Statistics (SATS). As the respondents had not yet taken a university course of statistics, but had listen the higher mathematics course, the research form was slightly modified. In the form 28 statements were used, for which respondents marked their agreement or disagreement on 5-point scale, ranging from disagree to agree. The participants were 172 students from Agronomy and Economics and Management faculties. The student’s attitudes were evaluated in 4 categories: affect, cognitive competence, value and difficulty. The results show the most complex and difficult parts of statistics learning. The survey of the results can be used for selecting appropriate teaching method.
Keywords: statistics; teaching methods